BOOK REVIEWS (Journal of Finance, 1951)
Book reviewed in this article: The Structure of American Industry . Edited by W alter A dams. Inflation in the United States, 1940–1948 . By L ester V. C handler. The Impact of Government on Real Estate Finance in the United States . By M iles T. C olean. Managerial Economics . By J oel D ean. Beckoning Frontiers . By M arriner S. E ccles. The Corporation Income Tax . By R ichard G oode. Economics of Investment . By J acob O. K amm. Public Finance . By M. S lade K endrick. The Dollar Shortage . By C harles P. K indleberger. The Theory of Investment of the Firm . By F riedrich and V era L utz. Money, Trade, and Economic Growth. Survey of United States International Finance, 1949 . By G ardner P atterson. Survey of United States International Finance, 1950 . By G ardner P atterson and J ack N. B ehrman.